Multilingualism an Asset to National Development: Nigeria in Focus - Oluchi, Lilian; Onyinyechi, Udushirinwa Ijeoma; Nonye, Nnani Henrietta (International Journal of Sustainability in Research, 2024)
Linguistic diversity in the world today has been an issue of growing social importance because a majority of all living languages are threaded in their continued existence. This brought about this research work: “Multilingualism as an asset to national development, a study of Nigeria”. the main aim of this research work is to appreciate the idea that multilingualism may be an asset of national development or a liability, to find a way of supporting it, the equilibrium points between multilingualism and national development, to give it some valuable suggestions which might be of help in language planning in a multilingual and multicultural setting like Nigeria. to bring this to the limelight, some research works were carried out as the researcher shared out some questionnaires, of which the respondents were a total of one hundred copies were collected for the research, the respondent is the students of English department and from other departments in Madonna University Okija. With a percentage and a frequency table, the data were properly analyzed. The outcome or result obtained showed that multilingualism or linguistic diversity did not project or promote disintegration in the country; rather the linguistic diversity in Nigeria has been a national resource that helped to move the country forward and not take multilingualism to be an instrument for national disintegration. In conclusion, the researcher made some recommendations that both the people at the helm of affairs should help in promoting national development through the use of multilingual policy in the country and the dissemination of information materials to the public like newspapers, posters, computer applications and programs to promote multilingualism.